Diversity And Distribution Of Vertiginidae (Mollusca: Gastropoda) In The Langkawi Islands, Kedah - Razalli, Norhanis Mohammad (2011)
A study was conducted on the diversity and distribution of microsnails from the family Vertiginidae at 16 locations that spreads across the limestone outcrops of the Langkawi Islands in the northern Straits of Malacca. A total of 10 species of vertiginids from three genera were identified with seven species from the genus Gyliotrachela, namely, G. depressispira, G. hungerfordiana, G. luctans, G. salpinx, G. transitans helioscopia, Gyliotrachela sp. 1 and Gyliotrachela sp. 2; two species from genus Paraboysidia, namely, P. frequens and P. serpa; and one unknown species from genus Nesopupa.